Quality improvement of manuka honey through the application of high pressure processing - Mohd Fauzi, Noor Akhmazillah (2014)
The quality of honey is known to be compromised when it goes through thermal processing due to its negative impact on the unstable and thermolabile honey components which originated from the nectar and bees themselves. This present work is undertaken to access the use of an emerging food preservation technique known as “High Pressure Processing” for treating honey, as an alternative to the conventional thermal processing. In this thesis, honey quality has been addressed by measuring the effects of high pressure processing parameters (pressure, time and temperature) on nutritional properties of honey, namely total phenolic content and antioxidant activity. Honey samples, contained in small pouches, were subjected to different pressures (200-600 MPa) at close to ambient temperatures (25-33°C) for different holding times (10 to 30 min). Thermal processing (49- 70°C) was also carried out for comparison purpose. Results demonstrated that high pressure processing operated at 600 MPa for 10 min has capability to increase significantly the total phenolic content and antioxidant activity by 47% and 30%, respectively. Besides, the result showed that high pressure processing can maintain the natural colour of honey which relates directly to consumer perception, while retaining its shear-thinning behaviour and viscosity with no significant changes (p > 0.05). High pressure processing can also control hydroxymethylfurfural (HMF) concentration in honey during process within the standard limit, 16.93 to 18.76 mg/kg (which is below than the maximum allowed limit of 40 mg/kg). This work also reveals that high pressure processing can enhance antibacterial activity of Manuka honey significantly. It shows an increase in the percentage inhibition of Staphylococcus epidermidis from 64.15 ± 5.86% to 84.34 ± 7.62% when honey was subjected to 600 MPa. Storage studies for one year at room temperature (25°C) demonstrated that high pressure-treated samples have a good retention to the physicochemical, nutritional and rheological properties of honey throughout storage, which confirms that the positive effect of high pressure on honey is not a temporary effect. Whereas, an insight study on the safety part showed that the Saccharomyces cerevisiae cell varied linearly with ° Brix, indicating that food compressibility has a significant role in the microbial inactivation.